A Systematic Review of the Usability of Telemedicine Interface Design for Older Adults - Huiqian He; Raja Ariffin Raja Ghazilla; Salwa Hanim Abdul-Rashid (Applied Sciences)
Telemedicine has the potential to support healthy aging in older adults; however, many applications fail to consider their specific needs and preferences, resulting in a limited number of effective options. This study systematically reviews the existing literature on interface design elements, attempts to link the elements with a Technology Acceptance Model (TAM), evaluates their usability for the elderly population, and highlights the social sustainability of telemedicine systems. A comprehensive search was conducted across the Web of Science, Scopus, PubMed, and CINAHL databases to identify existing research pertaining to the factors influencing usability, evaluation methodologies, and recommendations for telemedicine interfaces specifically designed for older adults. A total of 41 studies were analyzed, yielding a comprehensive summary of research methodologies and interface design elements from four key dimensions: the functional framework, interaction logic, visual design, and user experience. Our analysis identified prevalent usability challenges and provided actionable recommendations. Although the majority of studies focused on existing applications and usability testing, there was a notable gap in research addressing the cognitive and emotional needs of older users. Furthermore, many studies fell short in offering a comprehensive and detailed examination of design elements relevant to this user group. Based on the existing literature, this paper summarizes interface design elements suitable for elderly users, offering insights into user experience and usability. This study provides guidance for the interface design and development of telemedicine for old adults, offers suggestions on interface usability for practitioners in the medical industry, and also provides a reference value for the government in formulating relevant medical policies and for entrepreneurs in making investments.